2024
DOI: 10.1007/s40121-023-00915-w
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Molnupiravir in Japanese Patients with COVID-19: Final Report of Post-marketing Surveillance in Japan

Shohei Shinozaki,
Asuka Watanabe,
Masahiro Kimata
et al.

Abstract: Introduction Molnupiravir is an orally available prodrug of N -hydroxycytidine that received special approval for emergency treatment of coronavirus disease 2019 (COVID-19) in Japan in December 2021 and full approval in April 2023. To assess the real-world safety and effectiveness of molnupiravir in Japanese patients with COVID-19, we conducted nationwide post-marketing surveillance to collect data at registered institutions in Japan. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A study performed in an outpatient population in Quebec, Canada, during a BA.2 and BA.4/5 Omicron surge showed that in unvaccinated or incompletely vaccinated patients, the risk reduction in COVID-19-related hospitalization was 96%, while treatment of vaccinated patients with the antiviral had no significant effect on the risk of hospitalization and disease progression unless the patients were immunocompromised (transplant or neutropenic patients) or were over 70 years old [ 20 ]. A different study showed that Molnupiravir was also safe and effective among vaccinated Japanese patients with COVID-19, including the elderly and those with multiple comorbidities [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study performed in an outpatient population in Quebec, Canada, during a BA.2 and BA.4/5 Omicron surge showed that in unvaccinated or incompletely vaccinated patients, the risk reduction in COVID-19-related hospitalization was 96%, while treatment of vaccinated patients with the antiviral had no significant effect on the risk of hospitalization and disease progression unless the patients were immunocompromised (transplant or neutropenic patients) or were over 70 years old [ 20 ]. A different study showed that Molnupiravir was also safe and effective among vaccinated Japanese patients with COVID-19, including the elderly and those with multiple comorbidities [ 21 ].…”
Section: Introductionmentioning
confidence: 99%